State and Christian enlightenment - Malmenvall, Simon (Bogoslovni vestnik, 2024)
Mass elementary education powered by the state - one of the cornerstones of the processes of modernization - began to be established in continental Europe in the late eighteenth century. Increasingly centralized political institutions, with the decisive assistance of the school network, gradually created a bourgeois-industrial society centered on the performance-oriented individual committed to the state. The key to the spread of the school network and literacy was the coordination between Enlightenment ideas, state authorities, and ecclesiastical organizations. The situation in the Central European environments under consideration - Austria (part of which was also the territory of present-day Slovenia), Prussia, and other German lands - shows that the social role of education was strengthened by reform types of Christianity, which, based on the pursued harmony between the Church and State, sought to create a rational, industrious, and morally responsible individual.
Keywords: Central Europe; Christianity; elementary education; Enlightenment; General School Ordinance (1774); history; krščanstvo; osnovno izobraževanje; razsvetljenstvo; reform Catholicism; reformno katolištvo; school reforms; Splošni šolski red (1774); srednja Evropa; šolske reforme; zgodovina